Cognitive Profiles of Children with Low Motor Performance: A Contribution to the Validation of the WPPSI-IV - Julia Jascenoka; Franziska Walter (MDPI AG, 2022)
(1) Background: Developmental Coordination Disorder (DCD) is a common developmental disorder of preschool age. Children often show cognitive deficits in addition to motor problems. Various studies point in particular to problems in visual perception, working memory and processing speed. In this context, it is investigated whether the Wechsler Preschool and Primary Scale-IV (WPPSI-IV) is a suitable instrument for mapping these deficits in a valid and economical way. (2) Methods: The WPPSI-IV profiles of children with DCD (n = 12), below-average motor performance (n = 22) and a control group (n = 32) were compared. (3) Results: Children with DCD achieved significantly poorer test performance in the primary indices Verbal Comprehension, Visual Spatial, Processing Speed and Full Scale compared to a control group. Children with below-average motor skills, on the other hand, do not differ from the children in the control group. (4) Conclusions: The WPPSI-IV is a suitable instrument for diagnosing cognitive deficits in the context of DCD. The Fluid Reasoning and Verbal Comprehension indices should be used as a supplement to assess cognitive performance levels.